Hydroeconomic modeling of sustainable groundwater management. Issue 3 (23rd March 2017) - MacEwan, Duncan; Cayar, Mesut; Taghavi, Ali; Mitchell, David; Hatchett, Steve; Howitt, Richard
Abstract: In 2014, California passed legislation requiring the sustainable management of critically overdrafted groundwater basins, located primarily in the Central Valley agricultural region. Hydroeconomic modeling of the agricultural economy, groundwater, and surface water systems is critically important to simulate potential transition paths to sustainable management of the basins. The requirement for sustainable groundwater use by 2040 is mandated for many overdrafted groundwater basins that are decoupled from environmental and river flow effects. We argue that, for such cases, a modeling approach that integrates a biophysical response function from a hydrologic model into an economic model of groundwater use is preferable to embedding an economic response function in a complex hydrologic model as is more commonly done. Using this preferred approach, we develop a dynamic hydroeconomic model for the Kings and Tulare Lake subbasins of California and evaluate three groundwater management institutions—open access, perfect foresight, and managed pumping. We quantify the costs and benefits of sustainable groundwater management, including energy pumping savings, drought reserve values, and avoided capital costs. Our analysis finds that, for basins that are severely depleted, losses in crop net revenue are offset by the benefits of energy savings, drought reserve value, and avoided capital costs. This finding provides an empirical counterexample to the Gisser and Sanchez Effect. Key Points: Develop a hydroeconomic model with hydrologic response function embedded in an economic model that can be generalized to other subbasins Evaluate economic impacts of the California Sustainable Groundwater Management Act (SGMA) in example subbasins The present value net benefit of sustainable management equals 249 million, including energy, capital, and drought reserve benefits